Global information pickup underpins anticipation of tennis shot direction - Huys, R.; Cañal-Bruland, R.; Hagemann, N.; Beek, P. J.; Smeeton, N. J.; Williams, A. M. (Journal of Motor Behavior, 2009)
The authors examined the importance of local dynamical information when anticipating tennis shot direction. In separate experiments, they occluded the arm and racket, shoulders, hips, trunk, and legs and locally neutralized dynamical differences between shot directions, respectively. The authors examined the impact of these manipulations on resulting (display) dynamics and the ability of participants with varying perceptual skills to anticipate shot direction. The occlusion manipulation affected the display dynamics to a larger extent than did the neutralization manipulation. Although the authors observed a decrement in performance when local information from the arm and racket was occluded or neutralized and when information from the trunk and legs was neutralized, the results generally suggest that participants anticipated shot direction through a more global perceptual approach, particularly in perceptually skilled participants.